Preparing Teachers for Effective K-12 Online Learning in the Age of Disruptions: A Call for Transforming Teacher Education - Michael K. Barbour; Charles B. Hodges (Open Praxis)
In light of current or future pandemics, natural disasters, war, or personal preferences, remote or online learning is becoming increasingly common. This reality means that teachers need to be equipped with the skills necessary to effectively teach online. In this article the authors highlight the importance of preparing teachers with effective online teaching skills and knowledge, and suggest two areas for improvement: (1) research support for scholars to build a knowledge base to better understand effective online teaching, and (2) changes to teacher preparation programmes to better equip teachers for this changing reality. Before presenting these recommendations, a brief discussion of the state of online learning globally at the primary and secondary level (commonly referred to as K-12), as well as the limitations of existing teacher education, prior to the COVID-19 pandemic is provided.